Seismic retrofit of severely damaged beam-column RC joints using HPFRCC. (January 2023) - Ghaderi Barmi, Cirous; Saghafi, Mohammad Hossein; Golafshar, Ali
Abstract: The purpose of this paper is to use high performance fiber reinforced cement composites materials (HPFRCC) in seismic repair and retrofit of the concrete exterior beams-column joints without special seismic details with severe damage, considering the effect of slab and transverse beam. For this purpose, four external beam-column joints with scale ½ have been subjected to cyclic loading. Initially, two original joints without special seismic details suffered severe damage, which led to shear failure due to unconfinement and slip of beam rebars in the core. Then the damaged joints were repaired using HPFRCC materials and a similar load history was applied to the repaired specimens. The cyclic behavior of repaired joints was evaluated with the behavior of original specimens and the results were presented in the form of load bearing capacity, stiffness degradation, ductility, and dissipated energy. The results show that the use of HPFRCC materials in the joint core area of the repaired specimens has resulted in better confinement and integrity of the longitudinal rebars of the beam and column and in addition, has caused the flexural plastic hinge in the beam. This mechanism has improved the cyclic behavior and significantly increased the bearing capacity, energy dissipation and ductility in the repaired specimens.